Interaction-Driven Metal-Insulator Transition in Strained Graphene - Tang, Ho-Kin (2015)
The question of whether electron-electron interactions can drive a metal to insulator transition in graphene under realistic experimental conditions is addressed. Using three representative methods to calculate the effective long-range Coulomb interaction between π electrons in graphene and solving for the ground state using quantum Monte Carlo methods, we argue that, without strain, graphene remains metallic and changing the substrate from SiO2 to suspended samples hardly makes any difference. In contrast, applying a rather large—but experimentally realistic—uniform and isotropic strain of about 15% seems to be a promising route to making graphene an antiferromagnetic Mott insulator.